Oestrogen, progesterone, and androgen receptors in ovarian neoplasia: correlation between immunohistochemical and biochemical receptor analyses. Issue 3 (1st March 2000) - van Doorn, Helena C; Burger, Curt W; van der Valk, Paul; Bonfrér, Hans M G
Abstract : Aim —To investigate the correlation between immunohistochemical and biochemical steroid receptor analyses by measurement of oestrogen, progesterone, and androgen receptor status in ovarian neoplasia. Methods —Tissue samples were obtained from 27 ovarian neoplasms, including two borderline tumours. Immunohistochemical staining of the tissue slides was scored semiquantitatively, incorporating the intensity and percentage of positive staining (histoscore). Tumours with a histoscore of 10 or more were considered steroid receptor positive. The epithelial and stromal fractions of the tumours were analysed separately. To study the uniformity of receptor expression throughout a tumour, up to four samples were analysed. Results —Immunohistochemical histoscores of the oestrogen receptor in the epithelial fractions were significantly correlated with the biochemical oestrogen receptor values ( r = 0.408). Androgen receptor status in the epithelial fraction was correlated with that in the stromal fraction ( r = 0.741), while androgen receptor histoscores in the epithelial fraction correlated with the biochemical assay values ( r = 0.463). On biochemical analysis, 17 of the 27 ovarian tumours were oestrogen receptor positive and seven were progesterone receptor positive. On immunohistochemical analysis, eight tumours were oestrogen receptor positive and two were progesterone receptor positive. Biochemical analysis showed that 14 of the 26 tumours were slightly androgen receptor positive (10–50 fmol/mg protein), while all the others were negative. On immunohistochemical analysis, seven of the 26 tumours were androgen receptor positive. When two or more specimens from one tumour were analysed, marked differences in steroid status were found, especially in progesterone receptor and androgen receptor expression. Some parts of a tumour were steroid receptor positive, while other parts were negative owing to heterogeneity of expression. Conclusions —Immunohistochemical and biochemical analysis of steroid receptors in ovarian tumours correlated weakly or not at all. Heterogeneity of expression within a tumour and the presence of progesterone and androgen receptors in the stromal fraction partly accounted for this observation. Biochemical and immunohistochemical androgen receptor status was much lower than in previous reports.